The measurement of the surface energy of solids using a laboratory drop tower. (December 2017) - Calvimontes, Alfredo
Abstract This work presents a technique for the study and measurement of the interfacial energies of solid–liquid–gas systems. The instrument and the evaluation method for the measurements obtained by it, allow the analysis of the energy changes of sessile drops submitted to microgravity. A mathematical model based on the thermodynamic of wetting is applied to evaluate the interfacial energies as a function of the drop shape changes due to the effect of the release of gravitation during the experiment. The presented model bases on the thermodynamic equilibrium of the interfaces and not on the balance of bi-dimensional tensors on the contour line. For this reason, the model does not follow Young's equation as the current surface wetting characterization techniques usually do. Fluids: Microgravity releases the tension Gravity is shown to influence the shape of a small drop of water on a surface in a theoretical model developed by a researcher in Germany. Alfredo Calvimontes from BSH Hausgeräte GmbH demonstrates the importance of the droplet geometry in determining the interfacial energies. Surface tension strongly influences a water drop's shape, but it was thought that gravity played little role for very small drops. However, recent experimental work has suggested that this might not be true. Calvimontes develops a theoretical model that differs from the conventional approach of the two hundred- years-old Young's equation in that it assumes a thermodynamic equilibrium of the interfaces, rather than a balance of forces, on the solid-liquid-gas contour line. The model was supported by high-speed-camera images of droplets on various surfaces in free fall using a three-meter drop tower that allows quantifying the change of shape from normal gravity to microgravity.